Our present and future water supply - Walker, John A. (Statistical and Social Inquiry Society of Ireland, 1894)
Public attention has been directed to the water supply to the city and townships during the past year more than has been the case since the foundation of the Vartry system. It seemed to require some such event as the unexampled drought of 1893 to arouse the public mind from the state of lethargy into which it had fallen during the past quarter of a century. So constant had been the Vartry service, so abundant in quantity, and so excellent in quality, that the inhabitants of the city and townships believed it was inexhaustible, and in that belief they were satisfied to rest content. But those who were behind the scenes, who had an opportunity of guaging the inflow and outflow at the Roundwood reservoir, who were acquainted with the constantly increasing demand made upon that basin both by the increased area supplied and the wasteful extravagance of consumers, had a different tale to tell They knew that the Vartry was not an inexhaustible quantity; that under certain conditions it might fail altogether.
Read Tuesday, 13th March, 1894
Keywords: Water supply; Vartry system; 314.15